Epigenetic program of ontogenesis and hyperfunction theory: reinterpreting the mechanisms of aging - Salnikov, Lev (Frontiers in Aging, 2026)
This paper presents a comparative analysis of the relationship between aging, the epigenetic program of ontogenesis, and the main postulates of the hyperfunction theory. The discussion highlights points of convergence between these frameworks and proposes a unified interpretation. According to the hyperfunction theory, aging arises from the continued activity of growth and regulatory pathways after reproductive maturity, as more cells shift from proliferation to functional maintenance while retaining high metabolic and signaling activity. However, this process does not represent a simple enhancement of specialized cellular functions. Instead, it reflects a redistribution of intracellular resources from self-sufficiency to the performance of specialized functions. Building on earlier findings on genome methylation dynamics, we argue that the epigenetic program of ontogenesis regulates primarily the genomic regions responsible for cell differentiation. This unbalanced regulation results in a gradual drift of the active epigenetic landscape toward maladaptation. Consequently, the hyperfunctional state observed during aging is not the primary cause but a downstream effect of this one-sided epigenetic influence. Thus, the main cause of aging is not software errors in old age, but the lack of feedback between the activity of domestic and specialized genes in the body’s cells. The approach presented in the article points to the promise of new approaches to rejuvenation based on restarting the epigenetic program of cells. This direction is aimed at restoring the balance of genomic activity underlying aging and offers potential measures to restore genomic balance.